Strategies for Managing Former Coal Mine Land as a Tourism Destination (Case Study of Gubang Park, Loa Ulung Village, Kutai Kartanegara Regency) - Ananda, Putri Ayu; Fibrianto, Alan Sigit (Universitas Islam Sultan Agung Semarang, 2024)
Kutai Kartanegara Regency has abundant coal reserves but has become an area that leaves many pits without reclamation, leading to casualties. As is the case in Loa Ulung Village, there is a former coal mining pit that has been abandoned by the company since 1994. However, in 2020 this area changed into a tourism function, so a strategy is needed in managing coal mining land into tourism. This research aims to analyze the strategies used in the management of former coal mining land into tourism called Taman Gubang and its relationship with Max Weber's social theory. This study method uses qualitative research with a case study design explaining the phenomenon of a dark former coal mine land into Taman Gubang tourism. The observation results show that there are several strategies in managing mining land into Taman Gubang tourist destination, which are location, attractions, and marketing. Data analysis using Miles and Huberman, consisting of data collection, data reduction, data display, and conclusion drawing/verification. This study found that in the strategy of managing former coal mining land into Taman Gubeng tourism, there is a location selection strategy, not all coal mining pits can be used as tourism. The strategy of developing tourism attraction by carrying out the concept of Gubang Dua Lambung and marketing strategy does not only focus on promotion but considers the location of the former coal mine, price, rides, and culinary. In this strategy there are four social actions of Max Weber, which are instrumentally rational actions, the development of Taman Gubang tourism has an impact on improving the economy, opening up jobs, and tourism with local cultural characteristics. Actions on the basis of values based on social values. Affective actions of continuing the local culture of 'Gubang' into a tourism. Keywords: Land management strategy, coal mining, tourism